Pelaksanaan Supervisi Pembelajaran sebagai Potret Kinerja Guru dalam Mengajar - Amanati, Farida; Bakar, Abu; Windarti, Sulistyo (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The implementation of education was inseparable from the existence and important role of the teacher. The teacher was a determining factor in the success of education, so various educational innovations, especially in curriculum development and improving human resources, were always carried out as in Madrasah Tsanawiyyah Mazro'atul Huda Karanganyar Demak. For the quality of education to be optimally achieved, the implementation of the teacher's performance tasks must receive supervision, both from the Supervisor and the Principal. Supervision of the learning process was a form of quality assurance carried out internally to provide services for an effective and efficient learning process which was generally carried out by the principal regularly. The principal acts as a supervisor in supervising the learning process to create or develop better teaching and learning situations. Based on the results of the supervision that had been carried out, the average achievement score for the implementation of teacher learning was 92.59, categorized as very good. However, some indicators need to be improved because they had values below the average. These indicators were the delivery of competencies and activity plans including the involvement of students in learning. Furthermore, the assessment of learning academic documents averaged 90.47, categorized as very very. However, the availability of learning academic documents needs to be increased in the document section of the question grid, assessment instruments, records of assessment results, documents of results of analysis of competence achievements and documents of teacher professional development activities.